2002
DOI: 10.1086/341564
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of CerebralCryptococcus neoformansInfection after Fungemia

Abstract: The pathogenesis of cerebral infection after Cryptococcus neoformans fungemia in outbred mice was investigated. Confocal microscopy and cultures on ficoll-hypaque gradient-separated blood cells were used to detect yeasts in the cytoplasms of monocytes. In semithin brain sections, poorly capsulated yeasts were seen in macrophages in the leptomeningeal space, in monocytes circulating in leptomeningeal capillaries, or in the endothelial cells themselves, strengthening the hypothesis that monocytes and endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
199
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(222 citation statements)
references
References 39 publications
15
199
2
6
Order By: Relevance
“…This strain of mice was selected for its individual susceptibility to C. neoformans infection in previous studies showing the clinical relevance of this murine model. 10,18 Mice were housed 7 to 8 per cage in our animal facilities and received food and water ad libitum. This study was conducted in accordance with the EC guidelines for animal care [Journal Officiel des Communuté s Europé ennes, L358, December 18, 1986].…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This strain of mice was selected for its individual susceptibility to C. neoformans infection in previous studies showing the clinical relevance of this murine model. 10,18 Mice were housed 7 to 8 per cage in our animal facilities and received food and water ad libitum. This study was conducted in accordance with the EC guidelines for animal care [Journal Officiel des Communuté s Europé ennes, L358, December 18, 1986].…”
Section: Animalsmentioning
confidence: 99%
“…Fungemia is a bad prognosis factor during cryptococcosis in both HIV-infected and -non-infected patients 8,9 and is almost certainly a requirement for fungal dissemination and crossing of the blood-brain barrier (BBB). 10,11 Very little is known about the sequential events leading to disseminated meningoencephalitis, the major clinical presentation and cause of death during cryptococcosis. For a long time it was generally believed that invasion of the central nervous system (CNS) followed seeding of the leptomeninges and growth of "microcysts" along the perivascular Virchow-Robin spaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many pathogens use the host cell as a nutrient source to support rapid replication, thus acting as genuine intracellular parasites (1,2). The human fungal pathogen Cryptococcus is an intracellular parasite of macrophages (3,4) and is believed to exploit these host cells to traffic from the lung, the primary site of infection, into the central nervous system (5,6).…”
mentioning
confidence: 99%
“…The capacity of C. neoformans to directly invade the endothelial cell lining of cerebral blood vessels in vivo has been shown by experiments in which live organisms were injected intravenously into mice. Studies in which the infected brains were examined by histopathology showed the presence of C. neoformans cells either within or between the cerebral endothelial cells, indicating that the organism was crossing the blood -brain barrier by either a transcellular or paracellular route (Chretien et al 2002;Chang et al 2004). Using intravital imaging of live mice that had been injected with fluorescently labeled C. neoformans, it was observed that, although both live and killed organisms lodged in the cerebral capillaries, only live organisms were able to traverse endothelial cells and invade the brain ).…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%